PEMBELAJARAN FISIKA MENGGUNAKAN PENDEKATAN KETERAMPILAN PROSES PADA KONSEP USAHA BAGI SISWA SMP - Aprilia Londonaung; Tineke Rondonuwu (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
The skills approach is an approach that is in accordance with the character of Natural Sciences (IPA), especially Physics on the subject of Business. This study aims to improve understanding of the concept of physics by using the process in class VIII junior high school students. This research is a classroom action research (CAR) which according to Muhammad Afandi, PTK or CAR (Classroom Action Research) is used to solve problems that arise in class. Implementation follows the stages of planning, implementing actions, observing, reflecting and repeating after reflection on recommendations to continue to cycle II. The results showed that after the first cycle there were 40% of students who had not finished studying, and after continuing with the second cycle, there were 2 students (6.66%) who did not complete their studies or 93.34% of the students finished learning. Therefore, it is concluded that the use of the business concept approach in class VIII SMP can improve student learning outcomes.